COMPARISON OF DEFERIPRONE AND DEFERRIOXAMINE FOR THE TREATMENT OF TRANSFUSIONAL IRON OVERLOAD IN CHILDREN WITH BETA THALASSEMIA MAJOR - Waheed, Nadia; Ali, Shafqut; Butt, Muhammad Asghar (Journal of Ayub Medical College Abbottabad, 2014)
Background: Thalassemia major is the most common genetic disorder in Pakistan. The study was done to compare the efficacy and safety of the deferiprone with deferrioxamine for the treatment of iron overload in children with thalassemia major. Methods: This randomized controlled trail was conducted at thalassemia blood transfusion unit of Allied Hospital, Faisalabad (AHF)/District Headquarter Hospital (DHQ), Faisalabad. Thalassemia-Unit Hilal-e-Ahmar, Alizeb Foundation and Blood Bank Services Faisalabad from November 2010 to December 2011.Children with beta thalassemia major of age more than 2 years and less than 16 years with transfusion iron over load were randomly allocated to one of the two groups each comprising of 67 patients. One group received deferiprone given at a daily dose of 75 mg/kg in three divided doses orally while the other group received deferrioxamine at dose 50 mg/kg/24 hrs for 5 days/week as parental infusion. Changes in the serum ferritin level were assessed. Cardiac function and toxicity were also examined. Results: Serum ferritin was significantly reduced after 1 year in both treatment arms (p=0.01). Neutropenia observed in 13 (19.40%) non-splenectomized patients taking deferiprone. Transient elevations in ALT were observed in 3 (4.47%) children taking deferiprone. Left ventricular ejection fraction (LVEF) remained in normal range in both treatment arm but has decreased significantly in Deferrioxamine group compliance. Compliance was better in deferiprone as compared to deferrioxamine. Discontinuing percentage 2 (3%) vs 9 (13.43%). Conclusion: Deferiprone is a highly efficacious and safe chelation therapy for patients with thalassemia major who are non-compliant to Deferrioxamine. Deferiprone have an efficacy profile comparable to standard Deferrioxamine. Keywords: Thalassemia deferiprone, deferrioxamine iron over load